Laughter, humor and mockery of the Great Emigration in England - Marchlewicz, Krzysztof (Laughter, humour, satire, 2024)
Political emigration does not seem to favor merriment, cheerfulness and jokes. But refugees, like everyone else, feel the need for laughter and joy, and very often they are the best escape from the sorrow of exile. This article is an attempt to present what and under what circumstances made Polish political refugees who took refuge in Victorian Britain laugh. They often manifested their sense of humour during political disputes and mockingly presented both Russian tsarism and their opponents. They tame the unknown British environment and reacted to their own inferiority complex by joking about their British hosts. The male loneliness of emigrants meant that one of the favorite threads of jokes and mockery for them was female-male relations. Everyday life also provided them with numerous occasions for not necessarily malicious laughter. They laughed at themselves, their own weaknesses, unhealthy ambitions, and funny misunderstandings. The preserved archival sources indicate that many emigrants did not lose their sense of humour and were eager to express it in various forms, despite the hardships od the émigré existence.